کتاب المغازی للواقدی کے خصائص و امتیازات(ایک تنقیدی مطالعہ): Characterisitcs of Kitab Al-Maghazi (A Critical Study) - Muhammad Arshad Rana, Rana Ahmed Raza; Ahmad, Dr. Imtiaz (Al-Irfan, 2023)
After The Quran and the books on Prophetic traditions, the Maghazi books are the source on Prophetic Sirah. Chronologically the maghazi written in the first two centuries carry the most valuable material of Prophetic Sirah. Some books are based on the principles of Hadith collection, while others are in historic perspective. Among these, Maghazi of al-Waqidi has unique properties. Though Waqidi and his book carry some controversies but it also bears some unique charactertistics. These characteristics have merits as well as demerits. It was deemed appropriate to bring forth the attributes of this book. The following article highlights these characteristics of the book with pertinent examples.